2014
DOI: 10.1111/jpm.12133
|View full text |Cite
|
Sign up to set email alerts
|

Role of personal and family factors in alcohol and substance use among adolescents: an international study with focus on developing countries

Abstract: Most studies examining adolescent alcohol and substance use or abuse hardly include samples from developing countries. To bridge some gap, the prevalence and associated social correlates of alcohol and substance use and abuse was examined among a cohort of school-going adolescents sampled from seven developing countries. Alcohol and substance abuse was measured using the CRAFFT instrument, independent socio-demographic correlates were determined using regression models. A total of 2454 adolescents completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…Additionally, a healthy control group with comparable age, gender, education and socio-economic class was also observed in our study, since these data were previously related with bullying and substance misuse 13 , 12 , 13 …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, a healthy control group with comparable age, gender, education and socio-economic class was also observed in our study, since these data were previously related with bullying and substance misuse 13 , 12 , 13 …”
Section: Discussionsupporting
confidence: 53%
“…The prevalence of alcohol use in adolescents varies from 7.8% to 78.9%12 , 14 , 15 around the world and from 26% to 71% in Brazil 1621 There are studies in adolescents with specific CDs, generally with small samples and variable frequencies of alcohol use (4.8%-70%), such as juvenile idiopathic arthritis,22 obesity and overweight,23 asthma,24 cystic fibrosis and sickle cell disease 25.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior work indicated that early age of onset of alcohol use is associated with increased risk of problematic substance use and deviant behaviour at later age (Ryzin & Dishion, 2014). Also, other studies found that early age of onset of alcohol use was associated with later frequent substance use and problems with emotional regulation (Atilola et al 2014). …”
Section: Risk Factors Associated With Alcohol Use In the Last 12 Monthsmentioning
confidence: 99%
“…The few studies including data from developing countries in South America and the Caribbean highlight the relationship between child and adolescent maltreatment and increased risk of alcohol use (Longman, González, Meléndez, García & Gómez, 2011;. Other studies in South Africa and a review including 11 developing countries, stress the importance of research on personal and family factors related to alcohol use in adolescents in developing countries (Atilola et al, 2014), and on the association between psychopathology and alcohol use (Saban &Flisher, 2010). …”
Section: Purposementioning
confidence: 99%
“…Further sources suggest that there is an association between adolescents' school performance and substance use, and that students who use psychoactive substances are at a greater risk of performing poorly in school and vice versa (Bergen, Martin, Roeger, & Allison, 2005;Diego, Field, & Sanders, 2003;Ellickson, Tucker, & Klein, 2001). Other known studies have confirmed that PASU is closely associated with truancy and school exclusion among other behavioral problems during adolescence (Atilola et al, 2014;Kacwamu, 2010).…”
Section: Introductionmentioning
confidence: 95%